Land restoration and changing gender dynamics in the drylands of eastern Kenya - Crossland, Mary (Bangor University, 2019)
Presented by Mary Crossland (Bangor University / World Agroforestry Center), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.